HEALTH-RELATED QUALITY OF LIFE AND SOME RELATED FACTORS AMONG OLDER PATIENTS WITH KNEE OSTEOARTHRITIS - Nguyen, Trung Anh; Tran, Viet Luc; Nguyen, Thi Hoai; Nguyen, Thi Thu Huong (Tạp chí Sinh lý học Việt Nam, 2023)
Objectives: To assess health-related quality of life (HRQoL) and its associations with selected characteristics among older people with knee osteoarthritis (OA). Subjects and Methods: A cross-sectional study was conducted on 184 older patients with knee OA treated at National Geriatric Hospital from May to August 2022. HRQoL was assessed using the EQ–5D–5L questionnaire, and characteristics of knee OA were also collected. Results: The proportion of patients reporting difficulties in the dimensions of mobility, self-care, usual activities, pain/discomfort, and anxiety/depression was 88%, 68.9%, 66.1%, 90.8%, and 66.1%, respectively. HRQoL in the older age group was significantly lower than that in the younger age group, particularly in the mobility and usual activities dimensions (p<0.05). Patients with less severe knee OA had better HRQoL, especially in the mobility and pain dimensions. Lower Visual Analog Scale (VAS) pain scores were associated with better HRQoL. Regarding subclinical findings, synovial membrane thickening was significantly associated with HRQoL in the mobility, usual activities, and pain/discomfort dimensions, while the presence of bone spurs was significantly associated with HRQoL in all dimensions except mobility. All negative correlation coefficients indicated an inverse relationship between WOMAC pain, stiffness, and physical function scores and HRQoL, showing that higher WOMAC scores were associated with poorer quality of life. Conclusion: More than two-thirds of older patients with knee OA reported problems in at least one dimension of HRQoL. The findings highlight that the dimensions of the EQ-5D-5L are associated with age, severity of knee OA, VAS pain scores, and WOMAC scores.